Organisational commitment, job satisfaction and intention to leave among physicians in the public health sector of Cyprus: a cross-sectional survey - Gregoriou, Ioanna; Papastavrou, Evridiki; Charalambous, Andreas; Economidou, Eleftheria; Soteriades, Elpidoforos Soterakis; Merkouris, Anastasios (My University, 2023)
Organisational commitment, job satisfaction and intention to leave constitute important characteristics of health professionals' employment status. Our study aimed at investigating the level of organisational commitment, job satisfaction in association with intention to leave among physicians.
Keywords: Epidemiology; Organisational development; Public health; Quality in health care